Answer:
C. There is only one solution: [tex]x = 2[/tex]. The solution [tex]x = 1[/tex] is an extraneous solution.
Step-by-step explanation:
Given:
The equation is:
[tex]\frac{1}{x-1}+\frac{2}{x}=\frac{x}{x-1}\\\frac{x}{x(x-1)}+\frac{2(x-1)}{x(x-1)}=\frac{x}{x-1}\\\frac{x+2x-2}{x(x-1)}=\frac{x}{x-1}\\\frac{3x-2}{x}=x\\ 3x-2=x^2\\x^2-3x+2=0[/tex]
Now, we solve this quadratic equation by factoring.
[tex] x^2-3x+2=0\\(x-2)(x-1)=0\\x=2\textrm{ or }x=1[/tex]
Now, [tex]x=1[/tex] is an extraneous solution as at [tex]x[/tex] equal to 1, the equation is undefined.
Therefore, [tex]x=2[/tex] is the only solution. The solution [tex]x=1[/tex] is an extraneous solution.